Portfolio technical efficiency assessment with DEA: the case of the PSI-20 enterprises - Ferreira, N. B.; Oliveira, M.M. (8th International Conference on Computational and Financial Econometrics (CFE 2014), 2014)
Financial researchers have long been interested in the factors that explain differences in the enterprises financial performance. Following the general concept of efficiency which relates the difference between observed and optimal values of inputs and outputs, the efficiency of the individual companies of the Portuguese stock market is assessed using DEA methodology. With the interest income, depreciation, cost of goods, employees and the net sales as factors applied in a truncated regression, the technical efficiency (TE) scores of the PSI-20 enterprises index are explored in order to verify the major contributors to efficiency variability. The results revealed that TE is higher for the enterprises in communications, media and energy economic sectors whereas the construction has the lowest TE scores. The “employees” factor contribute statistically to the stock market inefficiency, thus the bigger the enterprise the lesser the efficiency. The factors “cost of goods” and “interest income” are also destabilized factors to the efficiency though without statistical significance.